Modern media era on social media consumer purchase decision of beauty products - Naina Mohamed, Rozita; Md Jusoh, Zuroni; Mohd Nizam, Husna Nisa; Mazlan, Habib (Malaysian Consumer and Family Economics Association MACFEA, 2022)
The influence of the modern media era on social media Malaysian consumers’ purchasing decisions on beauty products includes utilization of social media marketing, e-WoM, brand image and advertisement design. Entrepreneurs must understand consumers’ perspectives on how they make purchasing decisions. This is a quantitative cross-sectional study with a convenience sampling method. An online self-administrated questionnaire was conducted, and 210 valid questionnaires were collected. Descriptive analysis was performed to analyze the data. The results found that advertisement design was the most influencing factor with the highest mean score. It is followed by brand image and social media marketing. E-WoM was found to be the least factor influencing consumers’ purchasing decisions with the lowest score that less than 4.0. The finding of this study is expected to contribute to the rapid growth of beauty industry research on social media. It will help organizations to craft and utilize social media with the appropriate strategy to their advantage. Entrepreneurs can initiate to perform attractive advertisements by predominating the brand image in social media.